A circulating tumor cell-based digital assay for the detection of EGFR T790M mutation in advanced non-small cell lung cancer. Issue 26 (11th June 2020) - Wang, Jing; Sun, Na; Lee, Yi-Te; Ni, Yiqian; Koochekpour, Rose; Zhu, Yazhen; Tseng, Hsian-Rong; Wang, Shuyang; Jiang, Liyan; Zhu, Hongguang
Abstract : A CTC-based digital assay to detect T790M mutation non-invasively, indicating peripheral arterial blood to be a more abundant CTC source. Abstract : Determining the status of epidermal growth factor receptor (EGFR) T790M mutation is crucial for guiding further treatment intervention in advanced non-small cell lung cancer (NSCLC) patients who develop acquired resistance to initial EGFR tyrosine kinase inhibitor (TKI) treatment. Circulating tumor cells (CTCs) which contain plentiful copies of well-preserved RNA offer an ideal source for noninvasive detection of T790M mutation in NSCLC. We developed a CTC-based digital assay which synergistically integrates NanoVelcro Chips for enriching NSCLC CTCs and reverse-transcription droplet digital PCR (RT-ddPCR) for quantifying T790M transcripts in the enriched CTCs. We collected 46 peripheral arterial and venous blood samples from 27 advanced NSCLC patients for testing this CTC-based digital assay. The results showed that the T790M mutational status observed by the CTC-based digital assay matched with those observed by tissue-based diagnostic methods. Furthermore, higher copy numbers of T790M transcripts were observed in peripheral arterial blood than those detected in the matched peripheral venous blood. In short, our results demonstrated the potential of the NanoVelcro CTC-digital assay for noninvasive detection of the T790M mutation in NSCLC, and suggested that peripheral arterial blood sampling may offer a more abundant CTC source than peripheral venous blood in advanced NSCLC patients.